Revisiting the concept of stress in forest trees at the time of global change and issues for stress monitoring - Filippo Bussotti (Elsevier, 2021)
The definition of stress comes from the physical sciences and refers to the ability of a force applied to a material to induce a deformation (strain). Unlike materials, living organisms and biological systems react to stress with responses to prevent or repair the damage. Plants exposed to stressful conditions move from an optimal (non-stressed) to sub-optimal state, until they reach a new equilibrium with the changed environmental conditions, through physiological, biochemical, and genetic pathways to cope with the new environmental conditions. Multiple fluctuating environmental pressures often act simultaneously, then the effects of individual stresses cannot be isolated. In natural ecosystems, plants, and plant communities, naturally adapted to harsh environments, are in equilibrium with their environment. This equilibrium can be considered as “optimal” albeit in relative terms (i.e., for a specific genotype at a specific site). The mechanisms of acclimatization and adaptation are important especially in trees, which are sessile long-living organisms, unable to escape from the worsening of the environmental conditions. Rapid climate change, with severe drought and heat waves, can have different effects in relation to their level of equilibrium before the impact (starting point). The new equilibrium can be defined in terms of fitness (capacity of individuals to grow and reproduce) and resilience (capacity to cope to stress and restore the condition prior to the disturbing factor). Field studies suggest that the photosynthetic efficiency can be preserved or restored in short time after the stress event, but resilience (measured in terms of dynamic of non-structural carbohydrates at tree level) may be more severely affected. The conservation and management activities of natural resources require monitoring the stress conditions of vegetation and predicting the possible changes in species composition and structure of communities and ecosystems. This is desirable to maintain and optimise the ecosystem services in a new environmental and future climate scenario.